Socio-economic and gender dynamics influence on the parental decision-making process for children's orthodontic care - A study in Madinah, Saudi Arabia - Asim A Almarhoumi (Wolters Kluwer Medknow Publications, 2024)
OBJECTIVES: To investigate the socio-economic and personal factors that impact parental decisions regarding orthodontic treatment for their children in Madinah, Saudi Arabia. MATERIALS AND METHODS: A digital self-administered questionnaire was employed to collect data from 414 parents, focusing on their motivations and barriers that influence their decision-making process regarding orthodontic treatment. RESULTS: Income level was the most significant factor in orthodontic decisions. Parents with higher incomes were twice as likely to choose orthodontic treatment for esthetic reasons compared to parents with middle incomes. The main incentive for seeking treatment was getting advice from dental professionals, with 60% of participants rating it as the most important factor. 34.5% of respondents identified cost as the main barrier, with middle-income parents being 151% more inclined to perceive it as a significant barrier compared to high-income parents. Gender dynamics revealed that mothers exhibited 48.9% greater concern regarding treatment costs compared to fathers, whereas fathers placed 2.105 times more importance on the orthodontist's reputation than mothers. CONCLUSION: Income levels, along with other socio-economic factors and gender dynamics, have a significant influence on parental decisions regarding orthodontic care. Personalized consultations that address these variations are crucial for improving communication between patients and practitioners and increasing the accessibility of treatment.